2016
DOI: 10.1126/scitranslmed.aai9188
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase 2A regulatory subunit PR70 is a gonosomal melanoma tumor suppressor gene

Abstract: Male gender is independently and significantly associated with poor prognosis in melanoma of all clinical stages. The biological underpinnings of this sex difference remain largely unknown, but we hypothesized that gene expression from gonosomes (sex chromosomes) might play an important role. We demonstrate that loss of the inactivated X chromosome in melanomas arising in females is strongly associated with poor distant metastasis-free survival, suggesting a dosage benefit from two X chromosomes. The gonosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…The PPP2R3B promoter region is unmethylated in healthy and cancerous tissues from males and females (Figure S1 ); thus, it is not subject to gender-related differential methylation or effects of X-chromosome inactivation in women. PPP2R3B is a gonosomal melanoma tumor suppressor gene (van Kempen et al, 2016 ). The amplimer from this region was used as a positive control for the Hpa II restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…The PPP2R3B promoter region is unmethylated in healthy and cancerous tissues from males and females (Figure S1 ); thus, it is not subject to gender-related differential methylation or effects of X-chromosome inactivation in women. PPP2R3B is a gonosomal melanoma tumor suppressor gene (van Kempen et al, 2016 ). The amplimer from this region was used as a positive control for the Hpa II restriction enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is not surprising, given that the tNOX gene resides on the X chromosome [13] and previous work showed that gender influences the survival of colorectal cancer patients [55,56]. Thus, the gender-related differences in clinical outcomes may reflect a dosage effect on genes expressed from sex chromosomes [57]. Using the online EMBL-EBI database (), we found that tNOX (ENOX2) expression was 2 Log2-fold enhanced in specimens from primary colorectal tumor patients with and without distant metastasis, as assessed in a microarray analysis [58].…”
Section: Discussionmentioning
confidence: 85%
“…The authors proposed that the copy-number sensitivity of this locus could explain the gender differences in melanoma incidence and survival. 35 It is possible to speculate that despite its location in the pseudoautosomal region 1 (PAR1) of the X chromosome, sex may alter the effects of PPP2R3B expression in the germline as well. As our patients with duplications were however of both sexes, and the correlation between PPP2R3B expression and survival in the melanoma trancriptomic data was independent of sex, we do not currently have any evidence for such an effect.…”
Section: Discussionmentioning
confidence: 99%